PERANCANGAN SISTEM INFORMASI MASYARAKAT PERUMAHAN PURI HUSADA AGUNG BERBASIS WEBSITE - Ridho Hilmawan; Fitri Yanti (Journal of Research and Publication Innovation, 2023)
The researcher intends to design a website-based housing information system with the aim of providing housing information such as information on facilities, contacts, and the latest housing news or the latest housing information. Goals Produce a simple, attractive, Puri Husada Agung housing information system website. modern and minimalist. Producing online-based information facilities as a substitute for information facilities which are still carried out door to door. Qualitative research methods with a descriptive approach because the authors can go directly to conducting interviews with respondents, observing, even in carrying out the analysis of writing this thesis, the authors use 4 methods of data collection namely: Observation, Interview, literature study, documentation, by applying the SDLC Waterfal Method development method the results of this study are very good and can be used by anyone there is a public need for housing information as a basic need in their lives. housing websites are also an effective way of promoting housing in a way that can be accessed by all people in society to expand the range of housing information and facilitate community access. wider scope, given additional features.